Relationship maintenance behavior and adult attachment: an analysis of the actor-partner interdependence model - Adams, Rebekah D.; Baptist, Joyce A. (My University, 2012)
Associations between relationships maintenance behaviors (positivity, openness, assurances, and sharing tasks) and anxious and avoidant attachment were examined in 265 married couples. Using structural equation modeling to employ the actor-partner interdependence model, the use of positivity, assurances and sharing tasks were found to be negatively associated with anxious and avoidant attachment for both husbands and wives. Being open and self-disclosing in marriage was not strongly associated with attachment. Results indicated that the use of maintenance behaviors in marriages could have the potential to foster increased security in partners. Research and clinical implications are discussed.
Keywords: Attachment; Relationship maintenance behavior; Marriage; Dyadic analysis; SEM; APIM